2019
DOI: 10.1177/1729881419830204
|View full text |Cite
|
Sign up to set email alerts
|

Q-learning trajectory planning based on Takagi–Sugeno fuzzy parallel distributed compensation structure of humanoid manipulator

Abstract: NAO is the first robot created by SoftBank Robotics. Famous around the world, NAO is a tremendous programming tool and he has especially become a standard in education and research. Aiming at the large error and poor stability of the humanoid robot NAO manipulator during trajectory tracking, a novel framework based on fuzzy controller reinforcement learning trajectory planning strategy is proposed. Firstly, the Takagi–Sugeno fuzzy model based on the dynamic equation of the NAO right arm is established. Secondl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…NAO (Wen et al, 2019) robot shown in Figure 12 is a humanoid robot with biped walking. There is a laser scanner at the head of NAO robot.…”
Section: Methodsmentioning
confidence: 99%
“…NAO (Wen et al, 2019) robot shown in Figure 12 is a humanoid robot with biped walking. There is a laser scanner at the head of NAO robot.…”
Section: Methodsmentioning
confidence: 99%
“…From [33], it is known that if the sufficient conditions ( 18)-( 20) are satisfied by Theorem 1, the ellipsoid (31), which is inside the domain of attraction, is contractively invariant. Then, the following condition of actuator saturation is obtained by (10) and (14).…”
Section: Theorem 1 the It2 T-s Fuzzy System (mentioning
confidence: 99%
“…The T-S fuzzy model can also be used to solve the actuator saturation problem for nonlinear systems [7][8][9]. In order to develop the fuzzy controller design method, a so-called "Parallel Distributed Compensation" (PDC) method was proposed for the T-S fuzzy model [10][11][12][13]. However, the state of practical engineer systems or controllers may differ from the original due to service life and frequency.…”
Section: Introductionmentioning
confidence: 99%
“…14 Wen et al proposed a trajectory planning based on reinforcement learning, which is archived by applying the Q-learning algorithm. 15 Zajačko et al applied artificial intelligence to an automated quality control process through an automated error detection system. 16 Pivarčiová et al controlled and corrected the programmed mobile robot trajectory by implementing an inertial navigation system.…”
Section: Introductionmentioning
confidence: 99%